Chiral 1H NMR of Atropisomeric Quinazolinones With Enantiopure Phosphoric Acids - Wu, Chaofei; Liu, Hongxin; Li, Juan; Xiao, Hong-Ping; Li, Xinhua; Jiang, Jun (Frontiers in Chemistry, 2018)
A chiral phosphoric acid promoted enantioselective NMR analysis of atropisomeric quinazolinones was described, in which a variety of racemic arylquinazolinones such as afloqualone and IC-87114 were well recognized with up to 0.21 ppm ΔΔδ value. With this method, the optical purities of different nonracemic substrates can be fast evaluated with high accuracy.